Relapse prevention interventions for smoking cessation - Hajek, P; Stead, L; West, R; Jarvis, M (2005)
A number of treatments can help smokers make a successful quit attempt, but many initially successful quitters relapse over time. Several interventions have been proposed to help prevent relapse. To assess whether specific interventions for relapse prevention reduce the proportion of recent quitters who return to smoking. We searched the Cochrane Tobacco Addiction Group trials register in May 2013 for studies mentioning relapse prevention or maintenance in title, abstracts or keywords. Randomized or quasi-randomized controlled trials of relapse prevention interventions with a minimum follow-up of six months. We included smokers who quit on their own, were undergoing enforced abstinence, or were participating in treatment programmes. We included trials that compared relapse prevention interventions with a no intervention control, or that compared a cessation programme with additional relapse prevention components with a cessation programme alone. Studies were screened and data extracted by one review author, and checked by a second. Disagreements were resolved by discussion or by referral to a third review author. Sixty-three studies met inclusion criteria but were heterogeneous in terms of populations and interventions. We considered 41 studies that randomly assigned abstainers separately from studies that randomly assigned participants before their quit date.Upon looking at studies of behavioural interventions that randomly assigned abstainers, we detected no benefit of brief and 'skills-based' relapse prevention methods for women who had quit smoking because of pregnancy, or for smokers undergoing a period of enforced abstinence during hospitalisation or military training. We also failed to detect significant effects of behavioural interventions in trials in unselected groups of smokers who had quit on their own or through a formal programme. Amongst trials randomly assigning smokers before their quit date and evaluating the effects of additional relapse prevention components, we found no evidence of benefit of behavioural interventions or combined behavioural and pharmacotherapeutic interventions in any subgroup. Overall, providing training in skills thought to be needed for relapse avoidance did not reduce relapse, but most studies did not use experimental designs best suited to the task and had limited power to detect expected small differences between interventions. For pharmacological interventions, extended treatment with varenicline significantly reduced relapse in one trial (risk ratio (RR) 1.18, 95% confidence interval (CI) 1.03 to 1.36). Pooling of six studies of extended treatment with bupropion failed to detect a significant effect (RR 1.15, 95% CI 0.98 to 1.35). Two small trials of oral nicotine replacement treatment (NRT) failed to detect an effect, but treatment compliance was low, and in two other trials of oral NRT in which short-term abstainers were randomly assigned, a significant effect of intervention was noted. At the moment, there is insufficient evidence to support the use of any specific behavioural intervention to help smokers who have successfully quit for a short time to avoid relapse. The verdict is strongest for interventions focused on identifying and resolving tempting situations, as most studies were concerned with these. Little research is available regarding other behavioural approaches.Extended treatment with varenicline may prevent relapse. Extended treatment with bupropion is unlikely to have a clinically important effect. Studies of extended treatment with nicotine replacement are needed.